Small Farmers in High Value Chains: Binding or Relaxing Constraints to Inclusive Growth? - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2014)
Linking small farmers to modern markets, whether domestically or for export, increasingly entails participation in modern supply chains coordinated by contract farming. Concerns have been raised regarding the possible disadvantages from contract farming facing small farmers. Most empirical work points to a positive correlation between participation in contract farming and net farm income. Such a correlation fails to correct for endogeneity of participation; few studies have performed multivariate analysis with such a correction.This case study, based on a survey of smallholders in the tobacco industry, seems to be the first such application for the Philippines. The study finds that, correcting for endogeneity, participation in contract farming causes a sizable increase in farm profitability; moreover, participation appears to be biased toward smaller farm sizes. The findings are robust to the econometric method used and even definition of participation. This is further evidence to confirm that supply chains linking agribusiness with small farmers via contract schemes are a viable model of value addition and inclusive growth in rural areas. Policies should be implemented to support an enabling environment for expansion of supply chains.
Keywords: 330; Philippines; supply chain; contract farming; smallholders; treatment effect; instrumental variable